Infant leukemia and parental infertility or its treatment: a Children's Oncology Group report - Puumala, Susan E. (Oxford University Press, 2010)
BACKGROUND: Little is known about the potential risk factors for infant leukemia. With its very young age at diagnosis, exposures occurring in the perinatal period are suspected. Parental infertility and infertility treatment have been studied with regard to childhood cancer in general, but rarely in individual cancer subtypes. METHODS: A case–control study of infant leukemia was conducted through the Children's Oncology Group, including cases diagnosed from January 1996 to December 2006 and controls selected through random digit dialing and birth certificate tracing. Maternal phone interviews were conducted to obtain information about infertility, infertility treatment and demographic factors. All cases as well as subgroups defined by mixed lineage leukemia (MLL) translocation status and leukemia subtype were examined. Statistical analysis was performed using multivariate logistic regression models. RESULTS: No significant associations between infertility or its treatment and combined infant leukemia were found. In subgroup analyses, there was a significant increase in the risk of MLL− leukemia for children born to women not trying to conceive compared with those trying for <1 year for all types combined [odds ratio (OR) = 1.62, 95% confidence interval (CI) = 1.01–2.59] and for acute lymphoblastic leukemia (OR = 2.50, 95% CI = 1.36–4.61). CONCLUSIONS: There were no positive associations between parental infertility or infertility treatment and infant leukemia. While this is the largest study to date, both selection and recall bias may have impacted the results. However, for infant leukemia, we can potentially rule out large increases in risk associated with parental infertility or its treatment.